Internationalization Strategy for Sembalun Specialty Coffee to Meet Foreign Consumer Demand; Case Study of Kopikey SMEs, Lombok, Indonesia - Rosyihuddin, Muhammad; Sudarmiatin, Sudarmiatin; Bidhin, Rosmiza (PT FORMOSA CENDEKIA GLOBAL, 2024)
Indonesia has a rapidly growing coffee industry. Various regions in Indonesia have their own coffee characteristics and are an attraction for each region, one of which is Sembalun coffee in East Lombok Regency, Lombok Indonesia. The problems that occur in the internationalization of Sembalun coffee provide our motivation to investigate how the internationalization strategy for Sembalun Lombok specialty coffee works using the fishbone diagram analysis tool, by knowing the cause and effect or root of the problem. carry out exports in destination countries. The internationalization of Sembalun specialty coffee is a very important internationalization strategy for those wishing to compete in the global market and achieve sustainable growth.